2019
DOI: 10.1093/eurpub/ckz186.134
|View full text |Cite
|
Sign up to set email alerts
|

Direct and the Indirect Determinants of Weight-Control Behaviours among Adolescents

Abstract: Background Economic determinants such as socioeconomic inequalities and parents’ employment have a profound impact on the health of adolescents in terms of unhealthy weight-control behaviours (UWCB). In addition, various family factors may play a role in adolescents’ weight-control behaviours (WCB). This study examines the association among socioeconomic status, perceived family wealth, and number of employed parents and Israeli adolescents’ WCB and asks whether family variables (parental com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Much change can be initiated through lifestyle interventions although some prescriptions are available for adolescents to use [ 49 ]. Adolescent smoking is common among Mediterranean countries, and in both the medium- and high-risk groups, there were regular smokers (International Report), suggesting further work is needed to establish ways to reduce this risk [ 22 , 29 ]. The high-risk group consists of regular smoking, drinking, and physical inactivity, suggesting a set of concomitant behaviors that is multifactorial, mimicking the possibilities for adulthood behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much change can be initiated through lifestyle interventions although some prescriptions are available for adolescents to use [ 49 ]. Adolescent smoking is common among Mediterranean countries, and in both the medium- and high-risk groups, there were regular smokers (International Report), suggesting further work is needed to establish ways to reduce this risk [ 22 , 29 ]. The high-risk group consists of regular smoking, drinking, and physical inactivity, suggesting a set of concomitant behaviors that is multifactorial, mimicking the possibilities for adulthood behavior.…”
Section: Discussionmentioning
confidence: 99%
“…While behaviors implemented during one’s developmental years tend to continue into maturity [ 17 , 18 ], clustering these risk factors among adolescents may hasten atherogenesis [ 19 , 20 ]. A recent study demonstrated that poor diet factors, such as low fruit intake, were present in more than half of the adolescent population studied [ 21 , 22 , 23 ]. Moreover, risk factors tend to appear together [ 17 , 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation